When teachers Google physical literacy: A cartography of controversies analysis. (August 2022) - Young, Lisa; Alfrey, Laura; O'Connor, Justen
How physical literacy (PL) is presented on 'the web' (i.e. Google) has implications for how health and/ physical education (H/PE) teachers and coaches engage with and understand the concept, and ultimately how it is made to act in practice. This research sheds light on the type of PL content they are likely to encounter in their search via the web. Utilising Venturini's 'cartography of controversies' method, the top 100 Google search results for PL were analysed to observe and describe how PL is presented on the web, by whom and in the name of what. Findings show that PL has been 'framed' on the web by a heterogeneous network of actors who present different viewpoints, ideologies and suggested practices for PL within and across the contextual 'spheres' of education, sport and health. Further, the findings highlight how Google's algorithms prioritise and privilege particular PL viewpoints and ideologies. Consequently, variations in understanding and practices will be evident between H/PE teachers and coaches who only engage with the first page of Google results (top one to 10 URLs) and those who read more broadly. Rather than relying on Google's algorithms or policymakers' interpretations of PL that commonly serve the interests of the sport and health 'spheres' we suggest that H/PE teachers and coaches need to act as 'knowledge brokers' and thus be reflexive and aware of the multiple versions of PL that are presented on the web. This is especially important if they use the web as a form of professional development.